2004
DOI: 10.1007/s10545-005-0036-7
|View full text |Cite
|
Sign up to set email alerts
|

Body composition in young adults with inborn errors of protein metabolism—A pilot study

Abstract: The natural history of inborn errors of protein metabolism and the long-term effects of prescribed semisynthetic therapeutic diets are largely unknown. We assessed body composition, measuring body-fat mass and distribution, fat-free mass, total body protein, total body potassium, bone density and skeletal muscle mass, in young adults (age > 18 years; 6 female, 5 male) with inborn errors of protein metabolism maintained on long-term low-protein diets, compared with controls. Female patients were significantly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Some showed the consequences of a long-term protein-restricted diet (Kerstetter et al 2003): one-third of the patients had short stature and over 60% of those evaluated had a significantly low BMD. Formal assessment of body composition would be of interest in this group (Wilcox et al 2005). Currently there are no recommendations for protein intake in adult patients with organic acidaemias.…”
Section: Discussionmentioning
confidence: 99%
“…Some showed the consequences of a long-term protein-restricted diet (Kerstetter et al 2003): one-third of the patients had short stature and over 60% of those evaluated had a significantly low BMD. Formal assessment of body composition would be of interest in this group (Wilcox et al 2005). Currently there are no recommendations for protein intake in adult patients with organic acidaemias.…”
Section: Discussionmentioning
confidence: 99%
“…The diet needs to be adjusted for age and growth (see below) [17,47,106]. Since low protein diets may increase the risk of osteoporosis, bone density monitoring from time to time may be advisable [164,165]. …”
Section: Patient Monitoringmentioning
confidence: 99%
“…Recent studies have shown that the Mediterranean diet was able to improve the lipid profile also in children affected with chronic diseases, such as type 1 diabetes (Cadario et al, 2012) and hypercholesterolaemia (Giannini et al, 2014). In PKU patients, the impact of the IEPM diet on various CVD risk factors was described in some studies from Mediterranean countries, such as Greece (Schulpis et al, 2002), Italy (Galluzzo et al, 1985) and Spain (Colome et al, 2001), in addition to Europe (Hvas et al, 2006), Australia (Wilcox et al, 2005) and the USA (Moseley et al, 2002). The plasma lipid profile was reported in some studies with contradictory results.…”
Section: Discussionmentioning
confidence: 99%